Examining Tarot Interpretations In Smartphone Fortune Application In Terms of Text Type - Sargın, Meltem (Atlas Journal, 2023)
Since ancient times, people have wondered about the future and sought ways to get news from the future. One of these ways is fortune telling, which is very common and has many varieties. Fortune interpretations contain unique outlines and linguistic choices; thus, they are thought to make up a genre per se. Accordingly, in this study, tarot fortune-telling interpretations are examined in terms of genre characteristics. The corpus of the study was created from the tarot interpretations in Faladdin, a smart phone fortune-telling application. Register Analysis, which is based on Systemic Functional Linguistics and aims to reveal the contextual and structural features of texts, was used as a research method. In accordance with the method, the context of situation and the large- and small-scale structures of the texts were analyzed, and the functions of the linguistic choices were identified. Consequently, it has been determined that the texts in the corpus reflect the characteristics of spoken language, and linguistic choices are made for the purposes of informing and persuading. It is predicted that in parallel with technological developments, genre studies are gaining importance, and the findings from such studies will contribute to internet applications and artificial intelligence studies.